2022
DOI: 10.1371/journal.pone.0262252
|View full text |Cite
|
Sign up to set email alerts
|

Associations of breastfeeding history with metabolic syndrome and cardiovascular risk factors in community-dwelling parous women: The Japan Multi-Institutional Collaborative Cohort Study

Abstract: Objective The aim of the present study was to investigate the associations between breastfeeding and the prevalence of metabolic syndrome in community-dwelling parous women and to clarify whether the associations depend on age. Methods The present cross-sectional study included 11,118 women, aged 35–69 years. Participants’ longest breastfeeding duration for one child and their number of breastfed children were assessed using a self-administered questionnaire, and their total breastfeeding duration was approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The factors affecting development of MetS include young age at the time of menstruation, heavy weight, more number of pregnancies, as well as more years of menopause [ 39 ]. In spite of 13% increase in the odds of developing MetS per each child, which indicates existence of dose-response relationship, histories of breastfeeding for more than one month would lower this chance and has a protective effect against MetS [ 20 , 38 , 40 ], which is in line with the present study. Also, weight or its variations may be an effective intermediate of breastfeeding in the risk of developing MetS [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The factors affecting development of MetS include young age at the time of menstruation, heavy weight, more number of pregnancies, as well as more years of menopause [ 39 ]. In spite of 13% increase in the odds of developing MetS per each child, which indicates existence of dose-response relationship, histories of breastfeeding for more than one month would lower this chance and has a protective effect against MetS [ 20 , 38 , 40 ], which is in line with the present study. Also, weight or its variations may be an effective intermediate of breastfeeding in the risk of developing MetS [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported MetS prevalence among women as around 10–60% [ 20 , 38 40 ]. The reason behind the difference in the reported values of studies could be type of study, selection and volume of samples, examined age groups, racial as well as geographical differences, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Tørris and Bjørnnes [27] conducted a systematic review and meta-analysis on the association between breastfeeding and MetS, which suggested that lactation might play a protective role against MetS. In addition, Matsunaga et al [28] reported that a lower probability of MetS was associated with the longest total duration of breastfeeding (>0 months) compared to those under 55 years with no history of breastfeeding. Further research is required to investigate lactation duration and its potential role in ameliorating or reversing MetS and its components.…”
Section: Discussionmentioning
confidence: 99%
“…In international literature, there are several studies that demonstrate the protective influence of exclusive breastfeeding in preventing the onset of metabolic syndrome and diabetes mellitus, which seems to be more effective at younger ages. The beneficial effect of breastfeeding has even been observed in women with gestational diabetes [50,51].…”
Section: Metabolic Syndromementioning
confidence: 99%